AN IMPORTANT COMPONENT OF BASIC THERAPY IN CYSTIC FIBROSIS (MUCOVYSCIDOSIS) IN CHILDREN: DORNASE ALFA - O.I. Simonova (Педиатрическая фармакология, 2011)
Dornase alpha plays an important role in the basic treatment of cystic fibrosis, having three clinical effects: powerful mucolytic, anti-inflammatory and antibacterial. Early drug inclusion and its permanent administration in the basic therapy allows patients with cystic fibrosis to have an active life, with occasional illness recrudescence, long-lasting remissions, stable function of external respiration. The drug is appropriate to prescribe as preventive and curative for chronic bronchitis and chronic polypoid pansinusitis immediately if the diagnosis of «Cystic fibrosis» is established. The effectiveness of dornase alfa depends on strict adherence to the rules of its use. Key words: cystic fibrosis, chronic bronchopulmonary disease, mukostasis, children, chronic pansinusitis, nasal polyps, basic therapy,  dornase alfa, the rules of administration, inhalation therapy. (Pediatric Pharmacology. — 2011; 8 (5): 122–126.)